2013
DOI: 10.1103/physrevb.87.054514
|View full text |Cite
|
Sign up to set email alerts
|

Fermi surface reconstruction of superoxygenated La2CuO4superconductors with ordered oxygen interstitials

Abstract: Novel imaging methods show that the mobile dopants in optimum doped La 2 CuO 4+y (LCO) get self-organized, instead of randomly distributed, to form an inhomogeneous network of nanoscale metallic puddles with ordered oxygen interstitials interspersed with oxygen-depleted regions. These puddles are expected to be metallic, being far from half filling because of high dopant density, and to sustain superconductivity having a size in the range 5-20 nm. However, the electronic structure of these heavily doped metall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 58 publications
6
41
0
Order By: Relevance
“…By including μ in GBCSEs as applicable to LCO, appealing to an idea inspired by the work of Tacon et al [9] and using as input any of the observed values of the gap-to-T c ratio for 36 ≤ T c ≤ 40 K, we have been led to solutions for μ and λ that are "sensible". Sensible because we found a) μ to have a low value-in the meV range (recall that for elemental SCs, μ is in ≈2 -10 eV range), which is in accord with the assertion made in [14] and the values reported in [15], and b) λ to be less than 0.5, which is in accord with the Bogoliubov constraint as discussed in [5]. (18) and (19), respectively.…”
Section: Values Of the Smaller Gapssupporting
confidence: 76%
See 2 more Smart Citations
“…By including μ in GBCSEs as applicable to LCO, appealing to an idea inspired by the work of Tacon et al [9] and using as input any of the observed values of the gap-to-T c ratio for 36 ≤ T c ≤ 40 K, we have been led to solutions for μ and λ that are "sensible". Sensible because we found a) μ to have a low value-in the meV range (recall that for elemental SCs, μ is in ≈2 -10 eV range), which is in accord with the assertion made in [14] and the values reported in [15], and b) λ to be less than 0.5, which is in accord with the Bogoliubov constraint as discussed in [5]. (18) and (19), respectively.…”
Section: Values Of the Smaller Gapssupporting
confidence: 76%
“…We now draw attention to the fact that Fermi energies of HTSCs have of late been attracting considerable interest, partly because their low values are believed [14] to be the cause of high-T c s and partly because they shed light on the gap-structures of HTSCs. In the context of LCO it seems significant that, on the basis of a thorough theoretical investigation, Jarlborg and Bianconi [15] have recently reported three values for its Fermi energy: 60, 150, and 240 meV. We now recall that both the usual BCS equations and GBCSEs, Equations (5) and (8) …”
Section: μ-Incorporated Gbcses In the One-phonon Exchange Mechanism (mentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the methods have been published earlier [47,53,65,66]. The supercell Hg 12 Ba 24 Cu 12 O 48+2 is extended 6-and 2-lattice constants along x and y, respectively.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…The idea that a higher N (E F ) provides a larger gain in electronic energy from a superconducting gap, and hence stronger coupling constants and higher T C , is still valid at large disorder. How to modify the cuprate band structures in order to get higher DOS without destroying other properties might be difficult, perhaps ordering of impurities into stripes is a promising way [50].…”
Section: Disorder and Fluctuations In Cupratesmentioning
confidence: 99%